2022
DOI: 10.1155/2022/2371057
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of the Role of SLC2A3 on Prognosis and Immune Infiltration in Head and Neck Squamous Cell Carcinoma

Abstract: Background. SLC2A3 is upregulated in various cancer types and promotes proliferation, invasion, and metabolism. However, its role in the prognosis and immune regulation of head and neck squamous cell carcinoma (HNSCC) is still obscure. This study is aimed at exploring the prognostic and immunotherapeutic potential of SLC2A3 in HNSCC. Methods. All data were downloaded from TCGA database and integrated via R software. SLC2A3 expression was evaluated using R software, TIMER, CPTAC, and HPA databases. The associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…54 SLC2A3 exerts multiple biological functions in different cancers, including tumor EMT, ferroptosis, glycolytic reprogramming, drug resistance and immunity. [55][56][57][58][59] Immune cell infiltration analysis showed that SLC11A1 and SLC2A3 expression was positively correlated with the infiltration levels of neutrophils, macrophages, dendritic cells, CD4+ T cells and CD8+ T cells. Moreover, the higher the expression levels of SLC11A1 and SLC2A3, the lower the tumor purity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…54 SLC2A3 exerts multiple biological functions in different cancers, including tumor EMT, ferroptosis, glycolytic reprogramming, drug resistance and immunity. [55][56][57][58][59] Immune cell infiltration analysis showed that SLC11A1 and SLC2A3 expression was positively correlated with the infiltration levels of neutrophils, macrophages, dendritic cells, CD4+ T cells and CD8+ T cells. Moreover, the higher the expression levels of SLC11A1 and SLC2A3, the lower the tumor purity.…”
Section: Discussionmentioning
confidence: 99%
“…Reportedly, SLC11A1 not only predicts the prognosis of colorectal cancer and hepatocellular carcinoma 52,53 but also serves as a stratification indicator for immunotherapy or chemotherapy in glioma patients 54 . SLC2A3 exerts multiple biological functions in different cancers, including tumor EMT, ferroptosis, glycolytic reprogramming, drug resistance and immunity 55–59 . Immune cell infiltration analysis showed that SLC11A1 and SLC2A3 expression was positively correlated with the infiltration levels of neutrophils, macrophages, dendritic cells, CD4+ T cells and CD8+ T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently reported in the literature, SLC2A3 shows overexpression in the basal and suprabasal layer cells of OSCC, demonstrating increased glucose uptake [ 16 ]. Also, bioinformatics analyses by Chu predict that upregulated SLC2A3 may link to advanced clinical stages and lymph node metastasis [ 17 ]. Fernanda’s IHC analysis confirms high SLC2A3 expression is associated with advanced tumor stages, vascular invasion, and decreased disease-free survival [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The oncogenic potential of SLC2A3 has been extensively investigated. An overexpression or copy number gain of SLC2A3 has been witnessed in liquid and solid tumors [ 103 , 104 , 105 , 106 , 107 , 108 ]. For instance, high levels of SLC2A3 were associated with unfavorable outcomes in CRC, gastric (GC), and head and neck squamous cell carcinoma (HNSCC) [ 105 , 106 , 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…An overexpression or copy number gain of SLC2A3 has been witnessed in liquid and solid tumors [ 103 , 104 , 105 , 106 , 107 , 108 ]. For instance, high levels of SLC2A3 were associated with unfavorable outcomes in CRC, gastric (GC), and head and neck squamous cell carcinoma (HNSCC) [ 105 , 106 , 107 ]. Additionally, SLC2A3 seems directly targeted by miRNAs along tumorigenesis [ 109 , 110 , 111 ].…”
Section: Discussionmentioning
confidence: 99%